The influence of the socialization of society 4.0 skills on students' understanding of careers at SMK Muhammadiyah 2 Malang - Farhan, Ahmad Dhiauddin; Vergina, Nafa Septy; Al Maram, Zahra Hafizhoh; Fauzan, Lutfi; Ardiansyah, Yadis Putra; Putra, Nur Mega Aris (Universitas Negeri Malang, 2024)
Career understanding is a depiction of students' mastery of various career and world of work information to support career decision making. This study is a service that aims to see the influence of the socialization of society 4.0 skills on students' understanding of careers at SMK Muhammadiyah 2 Malang. The research design uses a quantitative design in the form of a Quasi-experimental one-group pretest-posttest design using the normality test (Kolmogorov-Smirnov and Shapiro-Wilk) and the Wilcoxon test to compare the average of two variables in one group involving 79 class XI students as research subjects . The research subjects are class XI spread across five departments, the departments in question are Visual Communication Design (DKV), Computer and Network Engineering (TKJ), marketing, Retail Business (BR), and accounting. Seminars are given for 4-5 hours on the same day. The results of the analysis of the normality test using both Kolmogorov-Smirnov and Shapiro-Wilk show a non-zero normal distribution (p = 0.000) because p (Sig.) < 0.05. Therefore, another test is needed using the Wilcoxon test with the analysis results showing a sig value. p-value = 0.000 (p < 0.05). This shows that career seminars have an influence in increasing students' knowledge regarding career understanding. So it can be concluded that the delivery of career material has provided students with a better understanding of SMK 2 Muhammadiyah Malang City. Keywords: Career Understanding; Vocational School; Society 4.0 Skills